Proud to call this land home - Abd Razak, Dzulkifli (2007)
To the youth of this country I have a message. You have a wonderful future ahead of you. Unlike us, you have a country free from any domination. You grow up with your heads held high as masters in your own country. As masters you have the privileges as well as your duties and responsibilities. The future of this country rests on you: whether our star rises or falls, it will be due to you solely. Therefore, be ready to serve her, to build her up and to give your life in her defence. You and I must be determined to make Malaya a place which we shall all be proud to call home. We have therefore a role to play and let us play it well. —Tunku Abdul Rahman